Four decades of research on quality: summarising, Trendspotting and looking ahead. (4th July 2021) - Carnerud, Daniel; Bäckström, Ingela
Abstract : The purpose of this paper is to identify and depict the key areas around which research on quality has orbited during the past 37 years. Additionally, this paper aims to explore longitudinal patterns and trends in the identified key areas. Thereby, this study aims to present new perspectives on the foundational elements and evolutionary patterns of research on quality as well as future directions. The paper applies data- and text modelling methodology to a chronological dataset covering 37 years and consisting of scientific journals specialising in research on quality; it also includes scientific journals with a broader spectrum of operations management (OM) research. The study identifies seven central topics around which research on quality has centred during this time period: Service Quality & Customer Satisfaction ; Process design & Control ; ISO Certification & Standards ; TQM - Implementation, Performance & Culture ; QM - Practices & Performance ; Reliability, Costs, Failure & Problems and Excellence - BEMs, Quality Awards & Excellence in Higher Education . The results also show that the total number of entries has risen constantly since 1980; however, there was a period of decline between 2000 and 2012, indicating that after almost four decades, research on quality is still vibrant and relevant.